Endgame, Its Opening and Closing Style: A Conversation Analytic Study - Zasqia Damai Aulia Shakti (Lingua Susastra, 2024)
Conversation Analysis (CA) is crucial in discourse studies, focusing on everyday interactions. This study examines the conversational styles in the Indonesian talk show Endgame, hosted by Gita Wirjawan. Previous research on Indonesian talk shows has primarily explored speech acts and pragmatic aspects, with little emphasis on openings and closings. This study addresses that gap by applying CA to analyze these segments in "Endgame" episodes. Using a descriptive qualitative method, the study analyzes data from the four most-watched Endgame episodes as of November 2023. The findings reveal that Endgame adopts a high considerateness style, characterized by slow-paced dialogue, pauses, and minimal interruptions, creating a relaxed and friendly atmosphere. The opening starts by greeting viewers, introducing guests, and highlighting their roles, set as a preview to the following discussion. Meanwhile, the closings provide insightful messages, maintaining a relaxed ambiance. By examining adjacency pairs and interactional patterns, this study enhances understanding of how Endgame shapes its conversational style and engages its audience, contributing to broader discussions on media communication and talk show sociolinguistics.